Treating for the Common Good: A Proposed Ethical Framework - Jaffe, H; Hope, T (2010)
To reduce the spread of the human immunodeficiency virus (HIV), Granich et al.1 (2009) have proposed a new strategy for universal voluntary HIV testing immediately followed by antiretroviral therapy. Although this proposal is likely to benefit the partners of those affected and thus promote public health, it is by no means clear that it benefits the infected people themselves and indeed it may be harmful. Since the proposal involves an intervention that is not clinically indicated, it falls foul of the normal ethical standards of clinical medicine, which is to act in the best interests of patients. Neither is it a measure that would be imposed under the protection of public health law on people who are seen as representing such danger to others that significant restrictions in liberty are appropriate. Thus, the proposal represents a third category of public health measure. We argue that a coherent ethical framework including a robust process is appropriate to proposals of this kind and that medical research offers a useful model since some research, like this proposal, is motivated not by the interests of the individual participants but by the common good. We outline some possible elements of such an ethical framework. © The Author 2010. Published by Oxford University Press.